The impact of policy-oriented agricultural insurance on China’s grain production resilience - Tao Zheng; Tao Zheng; Tao Zheng; Guiqian Zhao (Frontiers in Sustainable Food Systems)
IntroductionAs an effective tool and public welfare product of the state to support and benefit agriculture, policy-oriented agricultural insurance has unique advantages in dispersing agricultural risks and guaranteeing stable grain production and supply.MethodsBased on provincial panel data from 2002 to 2021, this paper analyzes the impact of policy-oriented agricultural insurance on grain production resilience. It constructs a comprehensive indicator system to assess grain production resilience and examines the impact of the insurance premium subsidy policy and the insurance development level on grain production resilience.ResultsThe study finds that policy-oriented agricultural insurance significantly improves grain production resilience and passes the robustness test. The heterogeneity analysis shows that the policy-oriented agricultural insurance development level in major grain producing areas has a significantly positive impact on grain production resilience, and the impact is higher than that in non major grain producing areas. Additionally, the impact of policy-oriented agricultural insurance on grain production resilience in high risk areas is more pronounced than that in low risk areas. At the same time, the mechanism analysis shows that policy-oriented agricultural insurance can have a positive impact on grain production resilience by improving agricultural technology progress, land transfer, and grain cultivation specialization.DiscussionThis paper reveals that policy-oriented agricultural insurance has a positive impact on grain production resilience and provides relevant policy suggestions for the government. This has a considerable impact on promoting sustainable grain production.